Easier Seen Than Done: Merely Watching Others Perform Can Foster an Illusion of Skill Acquisition. (April 2018) - Kardas, Michael; O'Brien, Ed
Modern technologies such as YouTube afford unprecedented access to the skilled performances of other people. Six experiments ( N = 2, 225) reveal that repeatedly watching others can foster an illusion of skill acquisition. The more people merely watch others perform (without actually practicing themselves), the more they nonetheless believe they could perform the skill, too (Experiment 1). However, people's actual abilities—from throwing darts and doing the moonwalk to playing an online game—do not improve after merely watching others, despite predictions to the contrary (Experiments 2–4). What do viewers see that makes them think they are learning? We found that extensive viewing allows people to track what steps to take (Experiment 5) but not how those steps feel when taking them. Accordingly, experiencing a "taste" of performing attenuates the illusion: Watching others juggle but then holding the pins oneself tempers perceived change in one's own ability (Experiment 6). These findings highlight unforeseen problems for self-assessment when watching other people.